Conditions Necessitating Secondary School Teachers’ Turnover in the Elliotdale Circuit, South Africa - Mohammed , Issah (African Journal of Education,Science and Technology (AJEST), 2024)
This study examines the conditions necessitating secondary school teachers’ turnover in the Elliotdale Circuit of South Africa. The qualitative research approach was adopted. The design used was a case study. The purposive sampling technique was used to select a sample size of twenty-two (22) participants, which comprised twelve (12) teachers, five (5) principals, three (3) teacher union representatives and two (2) subject advisors. Permission was sought from the provincial and district education authorities. Face-to-face, in-depth individual interviews were conducted through audio recording. The questions used were open-ended. Collected data were transcribed and analysed manually using the deductive thematic analytical method. Findings on the conditions necessitating secondary school teachers’ turnover in the Elliodale Circuit include the Department of Education's inadequacy in motivating existing and newly recruited teachers, delays in the processing of newly recruited teachers' salaries, teachers’ feeling of being undervalued, unappreciated and not acknowledged by the District Education, poor socio-economic conditions and the underdeveloped nature of the school communities, poor relations between the teachers and some of the departmental officials, strict monitoring of the teachers' work, long-distance travel to and from school daily coupled with the high cost of transport fares, the prevalence of crime, including burglaries and rape and inadequate opportunities for further studies and career advancement. Recommendations made were that the Dutywa Education District should work with the Provincial Education Office to process all newly recruited teachers’ salaries at the earliest possible time, the district should create opportunities for all teachers to further their studies, rural schools should be provided with adequate infrastructure like well-furnished offices, science and computer laboratories and libraries and teachers should be provided with secured flats or houses with electricity and running water.